Cointegration Entre Corruption Et Croissance Economique A Travers Le Canal De L’investissement : Evidence Empirique Moyennant L’approche ‘’ARDL Bound Testing’’ Dans Le Cas De La Tunisie - Hechmy, Badry (European Scientific Journal, ESJ, 2016)
This study focuses on the relationship between corruption and economic growth in Tunisia from 1987 to 2013, and is mainly interested in the role of discretion and distortion in public spending. To explore the relationship between the variables of interest, ARDL Bound testing approach of Pesaran and Shin (1999) was used. The empirical results show that corruption negatively affects long-term economic performance. And suggest that public investment large scale is not necessarily desirable in an environment characterized by corruption, because it results in a waste of public funds. However the estimation of an ECM model of short-term dynamics shows that corruption is associated with an increase in real GDP per head. The results support the idea that corruption undermines long-term economic performance and call for institutional reforms to improve the quality of governance as a prerequisite for extensive economic growth.